(Pyridyl)benzoazole palladium(ii) complexes as homogeneous catalysts in hydrogenation of alkenes and alkynes. Issue 13 (18th March 2016) - Ojwach, Stephen O.; Ogweno, Aloice O.; Akerman, Matthew P.
Abstract : Complexes1–6 form "cocktail" catalysts in the hydrogenation and isomerization of alkenes and alkynes where the active species are homogeneous. Abstract : Reactions of 2-(2-pyridyl)benzimidazole (L1 ), 2-(2-pyridyl)benzothiazole (L2 ) and 2-(2-pyridyl)benzoxazole (L3 ) with either [PdCl2 (NCMe)2 ] or [PdClMe(COD)] produced complexes [(PdCl2 (L1 )] (1 ), [(PdCl2 (L2 )] (2 ), [(PdCl2 (L3 )] (3 ) and [(PdClMe(L1 )] (4 ) in good yields. Treatment of1 with PPh3 gave the cationic complex [(Pd(L1 )ClPPh3 ]Cl (5 ), while reactions of4 with one equiv. of PPh3 and NaBAr4 (Ar = 3, 5-(CF3 )2 C6 H3 ) produced the cationic complex [(Pd(L1 )MePPh3 ]BAr4 (6 ). Single-crystal X-ray analysis has been used to elucidate the structure of complex6 . The complexes formed active catalysts in hydrogenation reactions of alkenes and alkynes. Hydrogenation of terminal alkenes was accompanied by isomerization to the internal isomers, while alkyne reactions involved a two-step process producing alkenes and the respective alkanes. While the kinetics data and formation of inactive palladium nanoparticles support the homogeneous nature of the active species, mercury drop experiments indicated a possible role of the nanoparticles in the re-generation of the active species.